'The Land to Forget Time': tourism, caving and writing in the Derbyshire White Peak. (18th August 2017) - Edwards, Jess
Abstract: This article explores the relationship between three cultural practices which engage with the subterranean limestone landscapes of the Derbyshire White Peak: showcave tourism, sport caving and literary landscape writing. It suggests that modern tourism and caving perform and represent the Peak 'underland' in distinctive but interrelated ways which have deep roots in the tourism of the past, as a landscape which is both wonderful and ordinary, solitary and sociable, ancient and everyday, and examines some contemporary landscape writing which draws on both representational conventions. The article argues that the White Peak landscape should be understood as a 'vertical' geography which is both physically and culturally multilayered, and suggests that this layeredness can become flattened in geographies which focus on the surface landscape and aim to capture a unified sense of place.